How to produce high specific activity tin-117 m using alpha particle beam. (September 2016) - Duchemin, C.; Essayan, M.; Guertin, A.; Haddad, F.; Michel, N.; Métivier, V.
Abstract: Tin-117m is an interesting radionuclide for both diagnosis and therapy, thanks to the gamma-ray and electron emissions, respectively, resulting from its decay to tin-117g. The high specific activity of tin-117 m is required in many medical applications, and it can be obtained using a high energy alpha particle beam and a cadmium target. The experiments performed at the ARRONAX cyclotron (Nantes, France) using an alpha particle beam delivered at 67.4 MeV provide a measurement of the excitation function of the Cd-nat(α, x)Sn-117 m reaction and the produced contaminants. The Cd-116(α, 3n)Sn-117m production cross section has been deduced from these experimental results using natural cadmium. Both production yield and specific activity as a function of the projectile energy have been calculated. These informations help to optimize the irradiation conditions to produce tin-117 m with the required specific activity using α particles with a cadmium target. Abstract : Highlights: Cd-116( α, 3n)Sn-117 m. High specific activity Sn-117 m. Theranostic isotope.